The Influence of Price, Product Quality, And Security on Consumer Buying Interest in Online Shopee Shopping (Study on Labuhanbatu University Students’ Management Study Program) - Tanjung, Sonia; Simanjorang, Elida Florentina Sinaga; Limbong, Christine Herawati (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The purpose of this study was to examine the involvement of each of the variables analyzed and to see the effect of price, product quality, and security on consumer repurchase interest in online shopping (a case study of students at Labuhanbatu University, Management Study Program). In this study, the data collection method used by researchers was collecting data through primary data. The sample used in this study that has been examined is as many as 50 people with predetermined conditions. The data in this study were processed using the SPSS application ver. 24 by testing the hypothesis. The results showed that partially or by T-test the price variable had a positive and significant effect on the repurchase intention variable, this can be seen from T count 4.931 > 2.012 T table with a sig level of 0.000 < 0.05. The product quality variable has a positive and significant effect on the repurchase intention variable, this can be seen from the results of T count 7.536 > 2.012 T table with a significance value of 0.000 < 0.05. The security variable has a positive and significant effect on the variable of repurchase intention, this can be seen from the results of T count 5.108 > 2.012 T table with a significance value of 0.000 < 0.05. Meanwhile, together or through the F test, the price, product quality, and safety variables have a positive and significant effect on the Repurchase Interest variable. This can be seen from the results of F count 63.167 > 2.57 F table with a significance value of 0.000 < 0.05.